Successful Combination Therapies, Hospital Utilization Improvements among Late-Breaking Clinical Trials - Vinall, Phil (MD Conference Express, 2014)
This article reviews multiple late-breaking clinical trials focusing on combination therapy and hospital utilization improvements. Specific trials include the phase 3 AMBITION [NCT01178073], the Comprehensive Respiratory Outcome Management program, as well as trials investigating the use of noninvasive open ventilation, end-of-rotation handoffs, and 2 phase 3 randomized controlled studies [NCT01957163; NCT02119286] looking at umeclidinium for the treatment of COPD.